Novel Moraxella catarrhalis prophages display hyperconserved non-structural genes despite their genomic diversity. (December 2015) - Ariff, Amir; Wise, Michael; Kahler, Charlene; Tay, Chin; Peters, Fanny; Perkins, Timothy; Chang, Barbara
Abstract Background Moraxella catarrhalis is an important pathogen that often causes otitis media in children, a disease that is not currently vaccine preventable. Asymptomatic colonisation of the human upper respiratory tract is common and lack of clearance by the immune system is likely due to the emergence of seroresistant genetic lineages. No active bacteriophages or prophages have been described in this species. This study was undertaken to identify and categorise prophages inM. catarrhalis, their genetic diversity and the relationship of such diversity with the host-species phylogeny. Results This study presents a comparative analysis of 32 putative prophages identified in 95 phylogenetically variable, newly sequencedM. catarrhalis genomes. The prophages were genotypically classified into four diverse clades. The genetic synteny of each clade is similar to the group 1 phage familySiphoviridae, however, they form genotypic clusters that are distinct from other members of this family. No core genetic sequences exist across the 32 prophages despite clades 2, 3, and 4 sharing the most sequence identity. The analysis of non-structural prophage genes (coding the integrase, and terminase), and portal gene showed that the respective genes were identical for clades 2, 3, and 4, but unique for clade 1. Empirical analysis calculated that these genes are unexpectedly hyperconserved, under purifying selection, suggesting a tightly regulated functional role. As such, it is improbable that the prophages are decaying remnants but stable components of a fluctuating, flexible and unpredictable system ultimately maintained by functional constraints on non-structural and packaging genes. Additionally, the plate encoding genes were well conserved across all four prophage clades, and the tail fibre genes, commonly responsible for receptor recognition, were clustered into three major groups distributed across the prophage clades. A pan-genome of 283, 622 bp was identified, and the prophages were mapped onto the diverseM. catarrhalis multi-locus sequence type (MLST) backbone. Conclusion This study has provided the first evidence of putatively mobile prophages inM. catarrhalis, identifying a diverse and fluctuating system dependent on the hyperconservation of a few key, non-structural genes. Some prophages harbour virulence-related genes, and potentially influence the physiology and virulence ofM. catarrhalis . Importantly our data will provide supporting information on the identification of novel prophages in other species by adding greater weight to the identification of non-structural genes.